Encyclopedia of life sciences - O'Daly, Anne 1966-. (Tarrytown, N.Y. Marshall Cavendish, 2004)
An illustrated encyclopedia with articles on agriculture, anatomy, biochemistry, biology, genetics, medicine, and molecular biology.
Includes bibliographical references and indexes.
Keywords: Life sciences -- Encyclopedias; Biology -- Encyclopedias; Biology -- Encyclopedias; Life sciences -- Encyclopedias